Analysis of Raw Material Supply Chain Performance Assessment for Sustainable Marketing of Cassava Chips - Ananda, Agustia Rizka; Masithoh, Siti; Mubarakah, Syaima Lailatul; Pramartaa, Ikhsan Qodri; Kusumawati, Riny; Miftah, Himmatul (Universitas Djuanda, 2025)
One of the obstacles to fulfilling the demand for raw materials in the cassava chips industry is the inconsistency of quantity and quality, resulting in production imbalances; therefore, raw material supply chain management is needed. This study aims to analyze the performance of the raw material supply chain in the cassava chips industry. The research method is a survey through interviews with respondents. Determination of respondents using purposive and snowball sampling methods. The number of respondents was 44 people, consisting of industry players, intermediaries, and farmers. Data analysis used descriptive and quantitative analysis with the SCOR version 12 method. The results showed that the flow of the raw material supply chain in the cassava chips industry involves farmers and intermediaries (suppliers), cassava chips industry (manufacturers), agents (distributors), shops/resellers (retailers), and end consumers (customers). The average value of supply chain performance is 78%, including the good category. The lowest performance score is in the Plan process, at 65%; the source process is at 89%; the Make 71%; the return 74%; and the highest is the Deliver at 94%. Overall, the performance value is still not optimal, so improvements are needed in indicators that are still low by planning planting patterns, arranging planting schedules, sorting and standardizing raw materials, and improving raw material peeling techniques.